EVALUATION OF THE STRESS OF TRANSPORTING BROILER CHICKENS IN IRAQ ON SOME PRODUCTIVE, PHYSIOLOGICAL AND ECONOMIC CHARACTERISTICS - & et al., Al- obaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This experiment aimed for evaluating the stress and financial losses resulting from transporting broiler chickens  from farms to slaughterhouses under harsh Iraqi conditions. Data were collected from 18 farms, where 42,564 broiler chickens were transported to slaughterhouses. Depending on the time of journey, the marketed birds were divided into three groups: short-time (T1), medium-time (T2), and long-time (T3) that lasted 3, 6, and 9 hours, respectively. The total percentage of mortalities  resulting from transporting broiler was 0.46%, while the percentage of lost weight was 5.12%, thus the percentage of total losses resulting from transportation reached 5.58%. The overall percentage of mortalities and the percentage of lost weight increased with the increase transport period, as the percentage of mortality reached 0.08, 0.31 and 0.71%, while the percentage of lost weight amounted to 3.84, 5.12 and 5.63% when transporting broilers for 3, 6 and 9 hours, respectively. The financial losses resulting from the transport of broiler amounted to 12.627.275 Iraqi dinars, and the transport process led to a significant (P ≤ 0.01) increase in body temperature, H / L ratio, glucose and aspartate transaminase (AST) and alanine transaminase (ALT) enzymes in blood serum and highly significant (P ≤ 0.01) decrease in packed cell volume, hemoglobin concentration, cholesterol, triglycerides and uric acid. It is concluded that the transportation of broiler chickens in Iraq is very stressful and causes financial losses that exceed international rates.